Bridging Centralized Design and Local Realities: Implementation Strategies for the Family Information System (SIGA) in Bengkulu Province - Rian Firnanda Irsyadani; Jatmiko Yogopriyatno; Abdul Aziz Zulhakim (Pencerah, 2026)
This study examines how the Provincial Office of the National Population and Family Development Agency (Perwakilan BKKBN) of Bengkulu bridges the distance between the centrally designed Family Information System (SIGA) and the conditions under which it is actually run at the local level. Drawing on a qualitative descriptive case study, the research relied on in-depth interviews with four key informants who manage SIGA at the provincial office, supported by limited observation and documentation of official performance reports for 2023 to 2025, strategic plans, and budget records. A total of 202 coded interview units were analyzed through content analysis along the seven ITPOSMO dimensions of Heeks within the Design-Reality Gap framework. The analysis shows that the gap does not lie in the application itself but in the information and management dimensions, which together account for 57.4 percent of the coded evidence. The sharpest tension appears between the central demand for accurate, real-time, by name by address data and the uneven validation capacity, operator turnover, server instability, and limited operational budget found in the regions. Rather than redesigning the system, the office narrows this gap through tiered data verification, intensive mentoring and capacity building, and a combination of formal agreements and informal coordination. The study contributes to e-government research in Indonesia by applying the Design-Reality Gap to a vertical central-government unit running a national family data system, a setting that has rarely been studied, and by reading implementation success as a matter of organizational bridging rather than technical compliance.